Salicylate-Induced Suppression of Electrically Driven Activity in Brain Slices from the Auditory Cortex of Aging Mice - Namikawa, Minoru; Sano, Ayaka; Tateno, Takashi (Frontiers in Aging Neuroscience, 2017)
The prevalence of tinnitus is known to increase with age. The age-dependent mechanisms of tinnitus may have important implications for the development of new therapeutic treatments. High doses of salicylate can be used experimentally to induce transient tinnitus and hearing loss. Although accumulating evidence indicates that salicylate induces tinnitus by directly targeting neurons in the peripheral and central auditory systems, the precise effect of salicylate on neural networks in the auditory cortex (AC) is unknown. Here, we examined salicylate-induced changes in stimulus-driven laminar responses of AC slices with salicylate superfusion in young and aged senescence-accelerated-prone (SAMP) and -resistant (SAMR) mice. Of the two strains, SAMP1 is known to be a more suitable model of presbycusis. We recorded stimulus-driven laminar local field potential (LFP) responses at multi sites in AC slice preparations. We found that for all AC slices in the two strains, salicylate always reduced stimulus-driven LFP responses in all layers. However, for the amplitudes of the LFP responses, the two SAM strains showed different laminar properties between the pre- and post-salicylate conditions, reflecting strain-related differences in local circuits. As for the relationships between auditory brain stem response (ABR) thresholds and the LFP amplitude ratios in the pre- vs. post-salicylate condition, we found negative correlations in layers 2/3 and 4 for both strains, and in layer 5 in SAMR1. In contrast, the GABAergic agonist muscimol (MSC) led to positive correlations between ABR thresholds and LFP amplitude ratios in the pre- vs. post-MSC condition in younger SAM mice from both strains. Further, in younger mice, salicylate decreased the firing rate in AC L4 pyramidal neurons. Thus, salicylate can directly reduce neural excitability of L4 pyramidal neurons and hereby influence AC neural circuit activity rather than indirectly influence excitability via GABAergic modulation. That we observed age-dependent effects of salicylate and varied GABAergic sensitivity in the AC among mouse strains with hearing loss implies that potential therapeutic mechanisms for tinnitus may operate differently in young vs. aged subjects. Therefore, scientists developing new therapeutic modalities for tinnitus treatment should consider using both aged and young animals.